Diagnostic Assessment of Secondary School Students’ Readiness and Achievement of Fiqh Learning Objectives Through the Jigsawproach - Nusaibah; Ashif Az Zafi; Elok Wahyu Febriani (Pendidikan Agama Islam, Fakultas Ilmu Tarbiyah dan Keguruann, IAIN Syekh Nurjati Cirebon, 2026)
This study aims to determine student readiness and the effectiveness of achieving learning objectives in Fiqh (Islamic jurisprudence) through a Jigsaw-Type diagnostic assessments. This study employed a quantitative experimental method using a one-group pretest–posttest design, with diagnostic assessment sheets as the primary instrument. Data were primarily collected through pre-test and post-test, supported by prior observation and interviews conducted in Class VIII-C of MTs Negeri 1 Kudus. The validity test showed that three items were valid, while three others were excluded. The reliability test yielded a Cronbach’s Alpha value of 0.382, indicating low internal consistency. Furthermore, the paired sample t-test revealed a significant difference between pre-test and post-test scores (p<0.05), indicating an improvement in students’ learning outcomes. The findings indicate that diagnostic assessments play a crucial role in identifying students' initial readiness before Jigsaw learning and measuring the achievement of Fiqh learning objectives, as evidenced by a significant difference between pre-test and post-test scores (p=0.0001). Prior studies overlook diagnostic urgency in Jigsaw contexts, this research fills that gap by integrating pre-learning diagnostics to identify deficiencies, followed by adaptive Jigsaw interventions. Its novelty delivers not just effectiveness metrics (score improvements) but diagnostic feedback for tailored instruction, offering practical value for teachers, enhancing sustainable Fiqh learning at secondary level. Keywords: Diagnostic; Jigsaw; Student Readiness; Fiqh